Research on Landscape Design Based on Digital Technology. (November 2020) - Jun, Yan; Xian, Shan Xiao
Abstract: Firstly, this paper briefly analyzes the concept and development of digital technology. Then it deeply analyzes the application research of digital technology, including digital projection, VR technology and mixed reality. Finally, it expounds the application research of digital technology in landscape design, and puts forward the design strategy of improving the projection technology and VR virtual reality technology in digital technology from the current situation of landscape design development in China, so as to promote the integration of digital technology in landscape design development.